Variation of Total Electron Content in the Quiet and Disturbed Period and Their Correlation with Solar Wind Parameters - K.C., Poonam; Silwal, Ashok; Karki, Monika; Poudel, Prakash; Gautam, Sujan Prasad; Upadhyay, Devendra Raj (Journal of Nepal Physical Society, 2022)
Total electron content and electron density are the fundamental parameters that determine the main properties of the ionosphere. We have observed variation of Global Positioning System (GPS) derived Vertical Total Electron Content (VTEC) on three different geomagnetic events. The observed VTEC data is recorded from four GPS stations at different locations (87.26°E, 26.48°N); (85.79°E, 27.87°N); (84.57°E, 28.17°N), and (86.70°E, 27.81°N). To determine the severity of storms, we analysed the north-south component of interplanetary magnetic field (IMF-Bz), solar wind parameters- solar wind speed (Vsw) and solar wind dynamic pressure (Psw) ,and geomagnetic indices- Dst index, Kp index and Auroral Electrojet (AE). For all the studied event days, we observed intensified VTEC on geomagnetically disturbed days over quiet days. The VTEC enhancement was significantly high on the severely disturbed day, followed by the moderate storm and the minor storm.The study made to observe association of VTEC with different interplanetary and geomagnetic indices shows that during all studied event days, VTEC enhancement is positively correlated with Vsw, Psw, AE and Kp with cross-correlation coefficient above 0.8 at zero time lag and strong negative correlation with Dst index. In contrast, the correlation of IMF-Bz vary with the intensity of storm. Our finding show a significant variation in VTEC during the geomagnetic disturbances, supporting previous studies on ionospheric responses to geomagnetic storms as well as theoretical assumptions.